Control de Inventario en la Corporación Tecnológica Computacional - Murillo García, Kerly Raquel (2019)
Since ancient times the ancestors kept large quantities of food for times of drought is where the inventory arises, these ensured the subsistence in times of scarcity with the storage of goods and food calling this the existence of inventory. Therefore, today the control in the companies in the purchases and sales of the goods or services they provide is where the importance of proper handling of their inventories comes from, where the company will maintain an adequate accounting control and thus At the end of each period obtain a reliable status of the economic situation of the company. The inventory is part of the current asset that is ready for sale, that is, all the merchandise that the company owns and that is in stock valued at the cost of acquisition, for sale or productive activities.